P4 medicine for epilepsy and intellectual disability: nutritional therapy for inherited metabolic disease. Issue 1 (27th March 2019) - Tseng, Laura A.; Sowerbutt, Claire; Lee, Jessica J.Y.; van Karnebeek, Clara D.M.
Abstract: Early identification and treatment of inherited metabolic diseases (IMDs) are essential to prevent and minimize intellectual disability (ID) and epilepsy. The oldest form of treatment, nutritional modulation, has proved beneficial for many IMDs. These conditions represent a promising model for P4 medicine — predictive, preventive, personalized, and participatory — specifically through the interpretation of individual genetic, pathophysiological, and clinical characteristics. More than 1000 IMDs have been described, and for these different nutritional modulation strategies are applied, varying from substrate reduction, supplementation of vitamins for catalyzation of enzymatic reactions or supplementation of amino acids or other nutrients, to substitution for deficient or inactivated products. This review provides an overview of all IMDs presenting with epilepsy and/or ID amenable to nutritional modulation; these are 85 in number, belonging to 27 categories. Therapeutic strategies include protein-restricted diet, ketogenic diet, fat-restricted diet, lactose-restricted diet; supplementation of amino acids, carbohydrates, or others; and supplementation of vitamins or cofactors as well as a sick-day protocol. Nutritional therapies are generally safe, affordable, and accessible, but compliance is an issue. Three different types of response exist: (1) a positive effect on seizure control and/or psychomotor development; (2) efficacy in prevention of decompensation but ongoing damage occurs; and (3) insufficient insights or evidence to establish the treatment as effective. For the latter category, we describe pyridoxine-dependent epilepsy as a case vignette for P4 medicine, discuss the benefits and challenges of nutritional modulation in IMDs, and outline novel approaches and solutions.